ATURAN PERANG DI LAUT: SAN REMO MANUAL SEBAGAI SUMBER HUKUM INTERNASIONAL - Enny Narwati (Fakultas Hukum Universitas Gadjah Mada, 2008)
Law of naval warfare did not develop since Den Haag Convention in 1907. In 1994, international community was succeeding in making a regulation on naval warfare, which could be used by countries, which did naval warfare. That regulation called San Remo Manual. This Manual was prepared by famous international law scholars and members of navy around the world, in their individual capacity. The making of this Manual can be done with fully supported from International Institute of International Humanitarian Law and International Committee of the Red Cross. However, in international law, San Remo Manual does not have law enforcement and can not be the source of international law if there are armed conflicts between states in naval warfare. In order to be categorized as the source of international law, this manual should be in the form of an international convention or until all of the regulation in this Manual becomes an international customary law.